A systematic review of axillary nodal irradiation for the management of the axilla in patients with early-stage breast cancer. (June 2022) - Perera, F.; Baldassarre, F.G.; Eisen, A.F.; Dayes, I.; Engel, J.; Cil, T.; Kornecki, A.; George, R.; SenGupta, S.; Brackstone, M.
Abstract: Background: Given numerous publications and clinical trials regarding axillary management in breast cancer, we sought to summarize this complex literature to help clarify this field for clinicians. This systematic review focuses on the role of irradiation of the axillary nodes (locoregional nodal irradiation [LRNI]) in the management of the axilla in patients with early-stage breast cancer in various clinical settings. Methods: We searched MEDLINE and EMBASE databases, the Cochrane library, the proceedings of the ASCO, the ASTRO, the ESMO, the ESTRO, and the San Antonio Breast Cancer Symposium (2016–2019) meetings. The quality of the studies was assessed with design-specific tools. The study was registered in PROSPERO. Results: We included one systematic review, one individual patient data (IPD) meta-analysis, and five randomized controlled trials (RCTs). After axillary lymph node dissection (ALND), LRNI resulted in small benefits in breast cancer specific mortality, locoregional recurrence, and distant metastases-free survival but not overall survival. After a positive sentinel node biopsy (SLNB), LRNI may provide equivalent locoregional control and disease-free survival (DFS) compared to ALND with a lower risk of lymphedema. No randomized data is available for the neoadjuvant setting. Conclusions: The summary of the role of radiation, is relevant to radiation oncologists for choosing the correct cohort of patient requiring LRNI and to surgeons making clinical decisions regarding the timing and type of breast reconstruction offered to patients. Highlights: Node positive patients have modest benefits from regional radiation. Some node negative patient subsets may also benefit modestly from regional radiation. Regional nodal irradiation may be equivalent to axillary node dissection with less lymphedema. The optimal locoregional approach in the neoadjuvant setting is the subject of ongoing clinical trials.